1998
DOI: 10.1016/s0014-5793(98)01249-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the catalytic glutamate in the E1 component of human pyruvate dehydrogenase

Abstract: The pyruvate dehydrogenase complex catalyzes the conversion of pyruvate to acetyl-CoA. The first component (E1) converts pyruvate to bound acetaldehyde using thiamine diphosphate (ThDP) and Mg 2+ as cofactors. There is no 3D structure of E1 available but those of other ThDP-dependent enzymes show some similarities including a glutamate residue that assists in ThDP activation. Eukaryotic E1 has an K K P L L P structure and the conserved Glu VW of the L L-subunit was identified as a possible catalytic residue by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…Before determining the specific activity of the recombinantly expressed subunits of PfPDH E1 (a þ b, co-purified) as well as PfOxoDH E1, their purity was verified by SDS-PAGE (data not shown). The enzyme activity was followed by photospectroscopy at 600 nm using the electron acceptor 2,6-dichloroindophenol sodium salt (DCIP) as described previously 55 . The reaction buffer (50 mM KH 2 PO 4 and 2 mM MgCl 2 , pH 7) contained 200 mM TPP, 80 mM DCIP, 2 mM pyruvate/oxoglutarate and 50 mg enzyme.…”
Section: Methodsmentioning
confidence: 99%
“…Before determining the specific activity of the recombinantly expressed subunits of PfPDH E1 (a þ b, co-purified) as well as PfOxoDH E1, their purity was verified by SDS-PAGE (data not shown). The enzyme activity was followed by photospectroscopy at 600 nm using the electron acceptor 2,6-dichloroindophenol sodium salt (DCIP) as described previously 55 . The reaction buffer (50 mM KH 2 PO 4 and 2 mM MgCl 2 , pH 7) contained 200 mM TPP, 80 mM DCIP, 2 mM pyruvate/oxoglutarate and 50 mg enzyme.…”
Section: Methodsmentioning
confidence: 99%
“…ThDP is oriented by hydrogen bonds and van der Waals interactions, including the highly conserved l -glutamate residue, which is Glu85 in M. tuberculosis . This residue is implicated in catalysis as demonstrated by several mutagenesis studies. Substitution of Glu85 with alanine and with isosteric or isofunctional amino acid residues, e.g., l -glutamine or l -aspartate, respectively, led to a dramatic decrease in the activity of the enzyme in comparison to that of the wild type . Amino acid substitutions of conserved residues located in the immediate proximity of Glu85, His84, and Gln86 also led to a decrease in AHAS activity, suggesting that these residues are involved in the stabilization of the Glu85 side chain, keeping it interacting with N1′ of the ThDP .…”
Section: Ilvb/n Acetolactate (Acetohydroxyacid) Synthasementioning
confidence: 97%
“…This residue has been proposed [7] to initiate the ionization of C2 and it has been shown that mutation of this residue greatly diminishes the exchange of the C2 proton with solvent [12,13]. However, this finding is difficult to reconcile with the observation that mutation of this glutamate in transketolase [14], Z. mobilis PDC [15], yeast PDC [16] and human pyruvate dehydrogenase [17] results in enzymes with a significant residual activity.…”
mentioning
confidence: 99%